2001
DOI: 10.1111/j.1469-8749.2001.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between objectively measured feeding competence and nutrition in children with cerebral palsy

Abstract: This study aimed to investigate the prevalence of undernutrition in children with cerebral palsy (CP) and to determine the relation with feeding ability. Ninety children with CP from special needs schools were examined. Undernutrition was diagnosed on one or more of the following criteria: weight < 2nd centile, triceps or subscapular skinfold measurement < 3rd centile, mid-arm circumference <5th centile. Feeding competence was scored with respect to seven specific oromotor tasks using the Multidisciplinary Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(3 citation statements)
references
References 29 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Our data show higher prevalence of malnutrition defined by either indicator of nutritional status. These relatively higher prevalence rates than reported in previous studies on clinical samples both from low income [25] and high-income countries [26]. A recent study by Kakooza-Mwesige and colleagues in 2015, however, has reported 52% of cerebral children, who visited clinics, were malnourished [8].…”
Section: Discussionmentioning
confidence: 82%
“…Our data show higher prevalence of malnutrition defined by either indicator of nutritional status. These relatively higher prevalence rates than reported in previous studies on clinical samples both from low income [25] and high-income countries [26]. A recent study by Kakooza-Mwesige and colleagues in 2015, however, has reported 52% of cerebral children, who visited clinics, were malnourished [8].…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, the motor difficulties can also interfere with self-feeding [6]. All these factors can collectively affect food consumption, resulting in growth faltering among children with CP [28]. If those underlying issues remain unresolved, the gap between requirement and intake is likely to increase as the child grows, which could accelerate the growth faltering.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of term infants describes faltering weight associated with difficulties progressing with food consistencies in later infancy [18]. Eating a limited range of consistencies and OMD are associated with poor nutrition and growth in other populations [19][20][21][22][23]. Progress with food consistencies should be one of the aspects of feeding further evaluated in preterm infants.…”
Section: Discussionmentioning
confidence: 99%